Decolorization and Degradation of Reactive Red Dye-238 by using ZnO - ., Riyad Al-Anbari; ., Abdul Hamed Al-Obaidy; ., Eman Abd (Iraqi Journal of Civil Engineering, 2017)
Removal of reactive red dye (Cibacron Red FN-R) from simulated wastewater has been investigated as a function of solar advanced oxidation process. The photocatalytic activity using ZnO as a photocatalyst has been estimated. Different parameters affected the removal efficiency, including pH of the solution; initial dye concentration and H2O2 concentration were evaluated to find out the optimum value of these parameters. The results proved that, the optimal pH value was 8 and the most efficient H2O2 concentration was 100mg/L. Reduction of organic content for effluent solution was also monitored by measuring chemical oxygen demand (COD) to assess the degradation process. This treatment method was able to strongly reduce the organic content of reactive red dye-238 to 90% while the colour removal was 99%. It can be concluded, from these experiments, that the using of ZnO as a photocatalysis was exhibited as economical and efficient treatment method to remove reactive red dye-238 from aqueous solution by reducing its colour and COD value. Results were properly fitted to LH model.